Study of antioxidant properties of fractionated apple peel phenolics using a multiple-assay approach - Massini, L. (2017)
The recovery of antioxidant mixtures from fruit waste is an opportunity to find natural alternatives to synthetic compounds for further food applications. Target components are selected based on an understanding of their antioxidant properties in solvent systems of different composition before further food use. Phenolic antioxidants were extracted with an alcoholic solution from the peels of cv Bramley’s Seedling apple and then fractionated with solvents of different polarity. The composition of the extracts was analysed through identification of the main classes of phenolics and their components; the antioxidant and metal chelating capacity were assessed using chemical assays in solvent media with different characteristics. The phenolic composition and the type of solvent had an effect on the antioxidant behaviour of the phenolic extracts, especially in the presence of phases with different polarity (e.g. emulsified lipid in water). Apple peel phenolics, in particular hydroxycinnamic acids such as chlorogenic acid, could supply antioxidant protection not only through radical scavenging but also metal chelating capacity depending on the type of medium in which they are added and its environmental conditions. This should be considered when a multiple-assay strategy is adopted for the screening of plant phenolics as novel food antioxidants.